2022
DOI: 10.1177/00099228221084829
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Parental COVID-19 Vaccination Acceptance

Abstract: As the coronavirus pandemic continues to impact families and children, understanding parental attitudes and likely acceptance of the COVID-19 vaccine is essential. We conducted a statewide survey with a representative sample of parents in Tennessee focused on COVID-19 and influenza vaccine acceptance and perspectives. Data from 1066 parents were analyzed using weighted survey methods to generalize results to the state of Tennessee. About 53% of parents reported a likelihood to vaccinate their children against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Mothers showed more hesitancy regarding their children’s vaccination compared to fathers in almost all studies [ 52 , 57 , 68 , 75 , 79 , 91 , 92 , 93 , 98 , 106 , 116 , 133 ]; however, mothers also had higher willingness than fathers to vaccinate their children [ 83 , 88 , 105 , 115 , 120 ], although a few studies found no difference between mothers and fathers [ 87 , 130 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mothers showed more hesitancy regarding their children’s vaccination compared to fathers in almost all studies [ 52 , 57 , 68 , 75 , 79 , 91 , 92 , 93 , 98 , 106 , 116 , 133 ]; however, mothers also had higher willingness than fathers to vaccinate their children [ 83 , 88 , 105 , 115 , 120 ], although a few studies found no difference between mothers and fathers [ 87 , 130 ].…”
Section: Resultsmentioning
confidence: 99%
“…Obtaining influenza immunization was a positive contributing factor for parents to accept their children’s COVID-19 vaccination [ 57 , 59 , 65 , 68 , 77 , 86 , 104 , 116 , 121 , 140 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies examining COVID-19 vaccination intention [16][17][18], including a recent international meta-analysis [19], also have found that parents vaccinated against COVID-19 are much more likely to have their children vaccinated as well. Studies indicate that parents who are vaccinated against COVID-19 are also more likely to be vaccinated against influenza [20] and give greater weight to physician recommendations [17].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that a study found that parental acceptance of the COVID-19 vaccination for children was closely related to the acceptance of previous influenza vaccination. Specifically, parents who refused to have their children vaccinated against influenza were more than five times as likely to refuse to have their children vaccinated against COVID-19 than other parents [ 27 ].…”
Section: Methodsmentioning
confidence: 99%